2015
DOI: 10.1371/journal.pone.0142141
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Circulating Interleukin 33 Levels in Stable Renal Transplant Recipients at High Risk for Cardiovascular Events

Abstract: BackgroundThe Major Adverse Cardiovascular Events calculator (CRCRTR-MACE) estimates the burden of cardiovascular risk in renal transplant recipients (RTR). Our recent study of 95 RTR reported the 7-year median risk of cardiovascular events (CVE) to be 9.97%, ranging from 1.93 to 84.27%. Nearly a third (28.4%) of the cohort was above 20% risk for a CVE. Since interleukins (ILs) as part of the inflammatory response may play a role in the pathogenesis of cardiovascular disease (CVD), we extended this study to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Further efforts to define the CV risk profile of renal transplant patients should look beyond the factors considered in our analysis and focus on other potential risk factors that have emerged from recent association studies. 22,23 Finally, as all patients were recruited from the province of Ontario, our findings many not fully reflect the experience in other areas of Canada or in other health care settings.…”
Section: Discussionmentioning
confidence: 74%
“…Further efforts to define the CV risk profile of renal transplant patients should look beyond the factors considered in our analysis and focus on other potential risk factors that have emerged from recent association studies. 22,23 Finally, as all patients were recruited from the province of Ontario, our findings many not fully reflect the experience in other areas of Canada or in other health care settings.…”
Section: Discussionmentioning
confidence: 74%
“…There were few studies conducted regarding IL-33/ST2 and cardiovascular risk in patients with kidney disease. In a study conducted in 95 renal transplant patients by Mansell et al, they found that IL-33 levels were increased in patients with high cardiovascular risk as compared with patients with low cardiovascular risks [ 55 ]. In our study, it was found that increased IL-33 and ST2 levels were associated with endothelial dysfunction, ST2 was one of the predictors of endothelial dysfunction, and both IL-33 and ST2 were predictors of fatal and nonfatal cardiovascular events during the follow-up period of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Serum IL-33 and sST2 levels were reported to be positively associated with cardiovascular events, vascular injury, and mortality in CKD patients (Gungor et al, 2017). Circulating IL-33 levels are also positively associated with greater risk of adverse cardiovascular events in renal transplant recipients (Mansell et al, 2015). In the mouse, expression levels of IL-33 were found to be increased with renal injury induced by UUO, principally in interstitial myofibroblasts (Chen et al, 2016).…”
Section: Profibrotic Cytokinesmentioning
confidence: 99%